Development of Accounting System to Enhance Economic Strength for Women of Processing Fermented Fish Group at Ban Dong Tat Thong, Prang Ku District, Sisaket Province - Piyachat Thongpaeng (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This research aimed to develop an accounting system to enhance economic strength for women of processing fermented fish group at Ban Dong Tat Thong, Prang Ku District, Sisaket Province. The population of the participatory action research was 25 women from processing fermented fish group at Ban Dong Tat Thong. The instruments used in this research were questionnaires, interview form, observation form and SWOT analysis. The statistics used for data analysis were mean, frequency distribution and percentage. The findings revealed that the accounting system used by the women of processing fermented fish group at Ban Dong Tat Thong was a simple one. In addition, the document storage was without sorting accounting list by transaction category. The accounting process was not operated systematically as Generally Accepted Accounting Principles (GAAP). Regarding research process, there was a development of standardized accounting system divided into 4 systems: materials and production equipment, (3) Distributing raw materials and production equipment and (4) Selling and receiving cash payment.